Invasive Computing - Anantharajaiah, Nidhi; Asfour, Tamim; Bader, Michael; Bauer, Lars; Becker, Jürgen; Bischof, Simon; Brand, Marcel; Bungartz, Hans-Joachim; Eichler, Christian; Esper, Khalil; Falk, Joachim; Fasfous, Nael; et al. (FAU University Press, 2022)

Invasive Run-Time Support System (iRTSS) - Bauer, Lars; Henkel, Jörg; Hönig, Timo; Schröder-Preikschat, Wolfgang; Eichler, Christian; Gonzalez, Jeferson; Herzog, Benedict; Langer, Tobias; Maier, Sebastian; Rabenstein, Jonas; Raffeck, Phillip; Schmaus, Florian (Invasive Computing, 2022)
Invasive programs, as well as hardware designed specifically to run them, need an operating system that does not make applications pay for resources, functions or features that are not needed in operation. With this in mind, we provide in the following methods, principles and abstractions for the application-aware extension, configuration and adaptation of invasive computing systems. These are technically integrated into an invasive run-time support system (iRTSS), a highly scalable heterogeneous operating system that comes in various forms and ports (LEON, x86-64, AMD64, ARM64) depending on the use case. The system addresses special-purpose MPSoC-based as well as general-purpose multicore/manycore machine
Keywords: InvasIC; iRTSS; OctoPOS; Agent System

System Software for Resource Arbitration on Future Many-* Architectures - Schmaus, Florian; Maier, Sebastian; Langer, Tobias; Rabenstein, Jonas; Hönig, Timo; Bauer, Lars; Henkel, Jörg; Schröder-Preikschat, Wolfgang (2020 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2020)

Towards Taming the Computing Continuum: System Software for Future Many-Core Architectures - Schmaus, Florian; Maier, Sebastian; Langer, Tobias; Rabenstein, Jonas; Bauer, Lars; Henkel, Jörg; Schröder-Preikschat, Wolfgang (HiPEAC 2020, 2020)